2016
DOI: 10.1016/j.bjm.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of gyrA and parC mutations in fluoroquinolones-resistant Pseudomonas aeruginosa isolates from Iran

Abstract: The aim of this study was to examine mutations in the quinolone-resistance-determining region (QRDR) of gyrA and parC genes in Pseudomonas aeruginosa isolates. A total of 100 clinical P. aeruginosa isolates were collected from different university-affiliated hospitals in Tabriz, Iran. Minimum inhibitory concentrations (MICs) of ciprofloxacin and levofloxacin were evaluated by agar dilution assay. DNA sequences of the QRDR of gyrA and parC were determined by the dideoxy chain termination method. Of the total 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 28 publications
4
25
1
Order By: Relevance
“…The results of mutations detected in GyrA and ParC genes are consistent with previous reports on clinical isolates of P. aeruginosa adapted to BC [28][29][30][31] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of mutations detected in GyrA and ParC genes are consistent with previous reports on clinical isolates of P. aeruginosa adapted to BC [28][29][30][31] .…”
Section: Discussionsupporting
confidence: 92%
“…So Thr-83 -> Ile was shown to be the chief mechanism of fluoroquinolones resistance. This observation confirmed that the DNA gyrase was the primary target for fluoroquinolone resistance in the clinical isolates of P. aeruginosa [30] .…”
Section: Discussionsupporting
confidence: 75%
“…In addition, authors observed that the fitness cost was influenced by the genotype of the type III secretion system harbored by the isolates (Agnello et al, 2016 ). Moreover, the dominance of the gyrA Thr83Ile alteration often associated with the parC Ser87Leu change in fluoroquinolone resistant strains of P. aeruginosa (Higgins et al, 2003 ; Lee et al, 2005 ; Agnello and Wong-Beringer, 2012 ; Yang et al, 2015 ; Araujo et al, 2016 ; Nouri et al, 2016 ) argues strongly for the salient role of the double-threonine/serine mutations in selecting groups of bacteria with favorable fitness also in this species.…”
Section: The Energy Balance Associated With Multiple Qrdr Mutationsmentioning
confidence: 99%
“…The ciprofloxacin is widely used in the treatment of K. pneumoniae infections in recent years, and the increasing resistance to fluoroquinolones among K. pneumoniae has also been reported 5, 6. Fluoroquinolones act by inhibiting the action of target enzymes, DNA gyrase and topoisomerase IV, with both enzymes playing a principal role in DNA replication 7 . Some researchers think that alterations in the quinoloneresistance-determining region (QRDR) within DNA gyrase ( gyrA and gyrB ) and topoisomerase IV ( parC and parE ) are the major mechanisms one for fluoroquinolone resistance in K. pneumoniae 6 …”
Section: Introductionmentioning
confidence: 99%